Antithrombin, protein C and protein S: genome and transcriptome wide association studies identify 7 novel loci regulating plasma levels - Ji, Yuekai; Temprano-Sagrera, Gerard; Holle, Lori A.; Bebo, Allison; Brody, Jennifer; Le, Ngoc-Quynh; Brown, Michael R.; Martinez-Perez, Angel; Sitlani, Colleen M.; Suchon, Pierre; Kleber, Marcus E.; Emmert, David B.; et al. (medRxiv, 2022)
Objective Antithrombin, protein C (PC) and protein S (PS) are circulating natural-anticoagulant proteins that regulate hemostasis and of which partial deficiencies are causes of venous thromboembolism. Previous genetic association studies involving antithrombin, PC, and PS were limited by modest sample sizes or by being restricted to candidate genes. In the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, we meta-analyzed across ancestries the results from 10 genome-wide association studies (GWAS) of plasma levels of antithrombin, PC, PS free and PS total. - Approach and Results Study participants were of European and African ancestries and genotype data were imputed to TOPMed, a dense multi-ancestry reference panel. Each of 10 studies conducted a GWAS for each phenotype and summary results were meta-analyzed, stratified by ancestry. We also conducted transcriptome-wide association analyses and multi-phenotype analysis to discover additional associations. Novel GWAS findings were validated by in vitro functional experiments. Mendelian randomization was performed to assess the causal relationship between these proteins and cardiovascular outcomes.GWAS meta-analyses identified 4 newly associated loci: 3 with antithrombin levels (GCKR, BAZ1B, and HP-TXNL4B) and 1 with PS levels (ORM1-ORM2). TWAS identified 3 newly associated genes: 1 with antithrombin level (FCGRT), 1 with PC (GOLM2), and 1 with PS (MYL7). In addition, we replicated 7 independent loci reported in previous studies. Functional experiments provided evidence for the involvement of GCKR, SNX17, and HP genes in antithrombin regulation. - Conclusion The use of larger sample sizes, diverse populations, and a denser imputation reference panel allowed the detection of 7 novel genomic loci associated with plasma antithrombin, PC, and PS levels.
Gesehen am 12.11.2025